Accountability through public participation? Experiences from the ten-thousand-citizen review in Nanjing, China. (19th March 2022) - Li, Yanwei; Qin, Xiaolei; Koppenjan, Joop
Abstract: In this contribution, we report on an in-depth case study of the ten-thousand-citizen review in Nanjing, an initiative to deal with the accountability deficit with which many Chinese governments have to cope. Nanjing Municipality invited citizens to evaluate officials' performance, and their reviews influenced the scores of officials' remunerations and even their careers. On the basis of theory, in this study, we develop a typology that is used to analyse how the introduction of this new horizontal practice of "letting citizens judge" influenced the existing accountability relations and how these relationships evolved over time. Our findings show that citizens' involvement initially resulted in a practice in which types of accountability were mixed and resulted in a situation of multiple accountabilities disorder. Only gradually were accountability characteristics aligned and the accountability deficit and overload reduced. This demonstrates the difficulties and challenges of introducing horizontal accountability arrangements in existing accountability systems.